“Molecular trinity” for soft nanomaterials: Integrating nucleobases, amino acids, and glycosides to construct multifunctional hydrogelators - Li, Xinming (2012)
This highlight introduces the development of hydrogelators consisting of nucleobases, amino acids, and glycosides (i.e., molecular trinity), or nucleobases and amino acids (i.e., nucleopeptides). These novel small molecule hydrogelators self-assemble in water to form stable supramolecular nanofibers/hydrogels and exhibit useful biological properties (e.g., biocompatibility, biostability, and the ability to bind and transport DNA into live cells). The approach discussed here not only provides a new strategy to develop soft biomaterials as a form of nanomedicines, but also contributes to the understanding of molecular self-assembly in water by modulating the non-covalent interactions derived from the three basic building blocks used in living organisms.